Reliability analysis of the Revised Adult Attachment Scale (RAAS) instrument in the Malaysian context - Ahmad, Rosliza (Photonics, 2014)
The objective of this article is to discuss the reliability analysis of the Revised Adult Attachment Scale (RAAS) instrument in the Malaysian context. This instrument was developed by Collins (1996) and has been used in western countries to measure the adult attachment style dimension. Items for RAAS were translated to the Malay language to suit the Malaysian adults’ sample. The sample of this study comprised of Malay married couples. A preliminary test and real test were conducted to determine whether its coefficient reliability value achieved the standard. The results of preliminary test and real test showed that the value of coefficient reliability for each dimension in RAAS have fulfilled the standard (p>.70). Based on these findings, the RAAS is a reliable instrument to be used among Malaysian adults. Furthermore, this instrument can be used by marriage counselors to understand how does attachment between husbands and wives may be related to thecouples’ problem or it may serve as a resource for couples to build a greatrelationship.